Effects of intravenous romifidine, detomidine, detomidine combined with butorphanol, and xylazine on tear production in horses. (21st December 2018) - Leonardi, F.; Costa, G.L.; Dubau, M.; Sabbioni, A.; Simonazzi, B.; Angelone, M.
Summary: Sedation facilitates the ocular examination in horses. Alpha2‐adrenoceptor agonists are commonly used in equine practice. If the eye is painful, the combination of an α2‐adrenoceptor agonist and butorphanol provides a greater analgesic effect. Unfortunately, little is known about the effects of α2‐adrenoceptor agonists on equine Schirmer tear test I (STT I) values. The aim of the study was to assess the effects of intravenous romifidine, detomidine, detomidine combined with butorphanol, and xylazine on the STT I values in horses. Forty healthy client‐owned Italian saddle horses were enrolled. Horses received 0.04 mg/kg bwt of romifidine or 15 μg/kg bwt of detomidine or 10 μg/kg bwt of detomidine combined with 10 μg/kg bwt of butorphanol or 0.7 mg/kg bwt of xylazine intravenously. The Schirmer tear test strip was inserted into the lateral third side of the inferior conjunctival fornix for 1 min in each eye. The STT I measurements were performed before sedation and at 5, 15, 30, 60, 120 and 180 min after the administration of sedation. The data were analysed by ANOVA. Romifidine did not affect the STT I values. Detomidine significantly reduced the STT I values at 15 min (18.17 ± 0.97 mm/min). The combination of detomidine and butorphanol significantly reduced the STT I values at 30 and 60 min (17.44 ± 0.99, 15.81 ± 0.99 mm/min). Xylazine significantly increased the STT I values at 5, 15 and 30 min (25.17 ± 0.99, 26.72 ± 0.99, 28.07 ± 0.99 mm/min). The STT I values at 180 min were similar to those before sedation. These results suggest that the administration of xylazine or detomidine alone or combined with butorphanol is associated with significant changes in aqueous tear production, whereas romifidine does not affect the STT I values. Romifidine is therefore suitable for chemical restraint to measure tear production in horses.